PERAN GURU IPS DALAM MEMBENTUK SIKAP DISIPLIN DAN TANGGUNG JAWAB SISWA (Penelitian Deskriptif Kualitatif di kelas VIII-G SMP Negeri 26 Bandung) - Sri Bintang Karo Karo, - (2021)
Abstrak: Penelitian ini didasarkan karena peran guru IPS sangatlah penting dalam membentuk sikap disiplin dan tanggung jawab siswa. Tujuan penelitian ini adalah untuk mendeskripsikan: peran guru IPS dalam merancang program pembelajaran IPS yang mampu membentuk sikap disiplin dan tanggung jawab pada siswa kelas VIII-G di SMP Negeri 26 Bandung, hambatan yang dihadapi guru IPS dalam membentuk sikap disiplin dan tanggung jawab pada siswa SMP Negeri 26 Bandung, apa saja upaya guru IPS dalam membentuk sikap disiplin dan tanggung jawab pada siswa SMP Negeri 26 Bandung. Berdasarkan hasil penelitian, peran guru IPS dalam merancang program pembelajaran IPS dalam membentuk sikap disiplin dan tanggung jawab adalah sebagai organisator, yaitu menyusun silabus dan RPP dan menentukan model dan metode pembelajaran yang dapat menumbuhkan sikap disiplin dan tanggung jawab. Hambatan yang dihadapi guru IPS dalam membentuk sikap disiplin dan tanggung jawab ialah ketika guru sedang tidak dalam kondisi yang baik sehingga lebih cenderung tidak acuh dalam memperhatikan sikap peserta didik dan adanya tidak sepemahaman dari rekan-rekan sejawat guru dalam pemberian apresiasi yang terus-menerus. Upaya yang dilakukan oleh guru IPS dalam membentuk sikap disiplin dan tanggung jawab siswa SMP Negeri 26 Bandung ini dikatakan berhasil karena adanya penerapan model Skinner yang menerapkan adanya jadwal penguatan (schedule of reinforcement), guru juga melakukan pembentukan (shaping), modifikasi tingkah laku (behavior modification) dan generalisasi diskriminasi. Kata kunci: Peran Guru IPS, Disiplin, Tanggung Jawab. Abstract: This research is based on the fact that the social studies teacher's role is very important in forming students' attitudes of discipline and responsibility. The purpose of this study is to find out: the role of social studies teachers in designing social studies learning programs that are able to form discipline and responsibility attitudes in class VIII-G students at SMP Negeri 26 Bandung, the obstacles faced by social studies teachers in forming discipline and responsibility attitudes of Students in SMP Negeri 26 Bandung, what are the efforts of social studies teachers in forming discipline and responsibility through the Skinner Model for students of SMP Negeri 26 Bandung. The method used by the researcher is descriptive qualitative at SMP Negeri 26 Bandung. The subjects are social studies teachers and students of class VIII-G. Data collection techniques are through online interviews, preliminary observations, and documentation studies. Based on the results of the study, the role of social studies teachers in designing social studies learning programs in forming disciplined and responsible attitudes is as an organizer, that are compiling syllabus and lesson plans and determining learning models and methods that can foster discipline and responsibility. The obstacle faced by social studies teachers in forming an attitude of discipline and responsibility is when teachers are not in good condition so they are more likely to be indifferent in paying attention to the attitudes of students and there is different understanding from fellow teachers in giving continuously appreciation. The efforts made by social studies teachers in forming student discipline and responsibility through the Skinner Model for students at SMP Negeri 26 Bandung are successful because of the implementation of Skinner model which implements a schedule of reinforcement, the teacher also shapes the attitude (shaping), behavior modification and generalization of discrimination.